2006
DOI: 10.1136/bmj.38782.575868.7c
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of enhanced psychosocial care on antipsychotic use in nursing home residents with severe dementia: cluster randomised trial

Abstract: Objective To evaluate the effectiveness of a training and support intervention for nursing home staff in reducing the proportion of residents with dementia who are prescribed neuroleptics. Design Cluster randomised controlled trial with blinded assessment of outcome. Setting 12 specialist nursing homes for people with dementia in London, Newcastle, and Oxford. Participants Residents of the 12 nursing homes; numbers varied during the study period. Intervention Training and support intervention delivered to nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
450
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(476 citation statements)
references
References 18 publications
(21 reference statements)
17
450
3
6
Order By: Relevance
“…The absence of a shared understanding of how end of life is recognised, or at what point end of life is defined for people with dementia, means that research that focused on improving symptom assessment for people with advanced dementia, on needs assessment in care homes, and on communication and the involvement of people with dementia in decision making were not included in the review (Fossey et al, 2006;Hancock et al, 2006;Zwakhalen et al, 2006). Data extraction ceased in 2006, however a rapid review of research and reviews published up till 2008 (Birch and Draper, 2008;Di Giulio et al, 2008;Lorenz and Lynn, 2008) indicate that the research focus and methods and findings discussed in this paper have not dramatically changed, and that there are still very few intervention studies that include people with dementia who are living at home or in a care home.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a shared understanding of how end of life is recognised, or at what point end of life is defined for people with dementia, means that research that focused on improving symptom assessment for people with advanced dementia, on needs assessment in care homes, and on communication and the involvement of people with dementia in decision making were not included in the review (Fossey et al, 2006;Hancock et al, 2006;Zwakhalen et al, 2006). Data extraction ceased in 2006, however a rapid review of research and reviews published up till 2008 (Birch and Draper, 2008;Di Giulio et al, 2008;Lorenz and Lynn, 2008) indicate that the research focus and methods and findings discussed in this paper have not dramatically changed, and that there are still very few intervention studies that include people with dementia who are living at home or in a care home.…”
Section: Discussionmentioning
confidence: 99%
“…The number of days of antipsychotic use decreased by 72% in the education homes compared with 13% in the control homes (po0.001). A more recent study demonstrated that a training and support intervention delivered to nursing home staff decreased the use of antipsychotics (Fossey et al, 2006). Additionally, collaborative care management in primary care settings, when compared with augmented usual care, showed improvements in overall severity of neuropsychiatric symptoms (Callahan et al, 2006).…”
Section: Psychosocial and Psychotherapeutic Interventionsmentioning
confidence: 99%
“…Although the limited evidence of efficacy does limit the potential value of quetiapine, this is probably helpful in indicating that atypical agents have a less detrimental impact on quality of life than typical antipsychotics. Important studies have highlighted the potential of specific non-pharmacological intervention programs to improve key outcomes such as the use of unnecessary antipsychotic drugs (Rovner et al 1996;Fossey et al, 2006), mood (Teri et al, 1997;2003) and behavioral symptoms (Cohen-Mansfield et al, 2007) with person-centered training for care staff, or structured approaches such as exercise, social interaction, pleasant events or assessment of needs, but disappointingly few studies have directly evaluated the impact of these interventions on quality of life directly, or the impact of stopping antipsychotics on quality of life amongst care home residents with dementia. The Focused Intervention Training and Support (FITS) study, in a cluster randomized trial, demonstrated the capacity of a training program focused on person-centered care to significantly reduce the use of antipsychotic drugs in care homes (Fossey et al, 2006).…”
Section: Antipsychotics and Quality Of Lifementioning
confidence: 99%